Efeitos da fotobiomodulação a laser (660nm) associada às células tronco mesenquimais em queimaduras de espessura total: estudo in vitro e in vivo - Andrade, Ana Laura Martins de (2019)
Burning, a traumatic lesion of thermal origin affects organ tissues and may be classified according to the layers of affected tissue. The complexity of the tissue repair process has always made burning treatment a challenge, not only due to its severity but also due to its multiple complications. Photobiomodulation (PBM) therapy for burning, especially in the initial phases of the process, promotes better healing and shorter repair time. The use of stem cells is an area of cutaneous lesion treatment that has been greatly explored and has shown progress in the field of tissue engineering, especially with mesenchymal stem cells. The association of both therapies is believed to accelerate the burned tissue repair process, stimulating cell proliferation and aiding the growth of a tissue of quality. Thus, this study aimed to evaluate the laser PBM therapy (660nm) action on the mesenchymal stem cells (MSC) proliferation; identify the biological mechanisms involved in the laser PBM action; establish a efficient experimental model for full thickness burn; and investigate the association of the techniques (PBM and MSCs) on the treatment of full thickness burns. Thus, we performed fours studies, two in vitro and two in vivo. The in vitro studies were performed with two (2D) and tri (3D) dimensional cultures, using mesenchymal stem cells derived from adipose tissue (hASCs) and lase PBM with three different energies (1J, 2J and 6J), with four groups for 2D cultures and four groups for 3D cultures. The 3D culture used a gellan gum spongy-like hydrogel. In both cultures we evaluated the viability, cell proliferation, reactive oxygen species (ROSs) and the inflammatory mediator interleukin-8 (IL-8). The in vivo studies concluded that laser PBM stimulates hASCs proliferation, in addition to maintaining their viability, depending on the energy used in both cultures; in addition to contributing directly to the stimulation of the ROSs and acting in the IL-8 modulation in the 3D culture. The in vivo studies utilized 114 Wistar mice, 18 for the first and 96 for the seconds study. The first study was performed with the soldering iron burn method, with temperature of 150 ºC. The animals were randomized in three groups, G5: burned with 5 seconds of contact with the soldering iron; G10: burned with 10 seconds of contact with the soldering iron; and G20: burning with 20 seconds of contact with the soldering iron. Histopathologial analysis concluded that all groups resulted in full thickness burn, regardless of the time of application. For the second in vivo study, the animals were randomly distributed in four groups: CG: control group, LG: animals treated with lase PBM (660 nm) and 2 J of energy, TCG: animals treated with MSCs and GLCT: animals treated with laser PBM (660 nm and 2J of energy) plus MSCs). The groups treated with laser PBM received irradiations three times a week, in alternated days, for 21 days. The groups treated with MSCs received ten applications of cells in a total volume of 600 μL right after the burning. We performed photographic monitoring in the periods of 3, 7, 14 and 21 days after the beginning of the experiment to evaluate the lesion contraction. Animals were euthanized in four distinct periods (3, 7 , 14 and 21 days after the experimental procedure) and we collected blood and tissue for further histological, immunohistochemistry, immunoenzyme and birefringence analyses. We conclude that the association of MSCs and laser PBM was an efficient method to accelerate the repair process and formation of cutaneous tissue of quality.